PERCEPTIONS OF ADOLESCENTS PERINATALLY INFECTED WITH HIV REGARDING THE SELF-DISCLOSURE OF THEIR STATUS - Mpofo, Caroline; Jacobs, Issie (Social Work/Maatskaplike Werk, 2017)
Most children born with perinatally acquired human immunodeficiency virus (HIV) are now maturing into adolescence. From an ecological systems perspective, this qualitative study aimed to explore and describe the perceptions of adolescents who were perinatally infected with HIV (ApHIV) regarding the self-disclosure of their status. Semi-structured interviews were conducted with 10 ApHIVs and interpreted using thematic analysis. The findings of the study link participants’ perceptions to societal attitudes towards HIV and to adolescent developmental factors, which contribute to decisions either to self-disclose or not to self-disclose their status. Recommendations are suggested regarding support for ApHIVs